Crustal growth and deformational processes in the northern Gondwanan margin: constraints from the Évora Massif (Ossa-Morena zone, southwest Iberia, Portugal) - Pereira, M. F.
The aim of this article is to present a compilation of available information on the Évora Massif based on structural mapping, whole-rock geochemistry, recognition of metamorphic mineral assemblages, and geothermobarometry. In our view, transcurrent movements responsible for strong orogen-parallel stretching were dominant and had a major role in the geodynamic evolution of this part of Ossa-Morena zone (southwest Iberian Massif). Cadomian and Variscan orogenic events separated by a period of intense rifting were the cause for the composite distribution of zones with contrasting metamorphic paths, the structural complexity, the variety of lithological associations, and the sequence of deformation events and magmatism. The proposed geodynamic reconstruction for this segment of the northern Gondwana continental margin includes three main stages in chronological order: (1) Neoproterozoic accretion and continental magmatic arc developing, dismantling, and reworking, followed by late-“orogenic” magmatism; (2) Lower Paleozoic crustal thinning, block tilting, and mantle upwelling, induced by generalized rifting, leading to the formation of marine basins with carbonate platform sediments and thick accumulations of volcaniclastic and terrigenous sediments, contemporaneous with normal and enriched mid-oceanic ridge basalt–type magmatism; and (3) Upper Paleozoic transpressional orogenesis resulting from obliquity of convergence and the geometry of the involved blocks. The third stage includes the tectonic inversion of Lower Paleozoic basins, crustal thickening, the exhumation of high- to medium-pressure rocks and partial exhumation of high-grade metamorphic lithologies (controlled by local transtension and major detachments), the formation of synorogenic basins filled with volcanicsedimentary sequences, and finally, the emplacement of late Variscan granodiorites and granites.